PENGARUH PEMBERIAN PROBIOTIK EM-4 (Effective Microorganism-4) PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) - Devy Permata Sari; Eri Yusni (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Tilapia is a freshwater fish that has widely cultivated and is very popular among the community. In tilapia aquaculture, the most important factors are growth and survival rate as well as sufficient feed requirements. This research aims to determine the effect of EM-4 on commercial feed towards the growth and survival of tilapia, as well as knowing the number or frequency of EM-4 which is effective against the growth and survival rate of tilapia (Oreochromis niloticus). This research was conducted from April to June 2018. During the study of fish were given commercial food mixed with EM-4. Feed were given of 5% from body weight. The frequency of feeding were given 3 times a day at 08.00 am, 01.00 pm and 05.00 pm. The design that have been used in this study was Complete Randomized design with 3 treatments and 3 repititions namely : P1 ( EM-4 8 ml / kg commercial feed), P2 (EM-4 12 ml / kg commercial feed) and P3 (EM-4 16 ml / kg commercial feed). The results of these research were used analyzed by SPSS program. The results showed that the giving of EM-4 significantly affected the length and weight of fish but did not significantly affect the survival rate of tilapia. The higher growth of length and weight was found with P3 and mixed of EM-4 16 ml / kg of feed and the higher survival rate was found in P3 and mixed of EM-4 16 ml / kg commercial feed.Keywords: Effective Microorganism-4, Growth Rate